STRATEGI TOKOH LINTAS AGAMA DALAM MENGATASI KONFLIK PADA MASYARAKAT PLURAL: (Studi kasus di Desa Mopuya Selatan Kecamatan Dumoga Utara Kabupaten Bolaang Mongondow) - Budi Nurhamidin; Mashadi (Farabi, 2021)
This study discusses the Strategy of Interfaith Leaders in Overcoming Conflicts in Plural Communities by taking case studies precisely in Mopuya Selatan Village, West Dumoga Subdistrict, and this research is a qualitative research focusing on field studies. In this study also aims as material recommendations for other areas that are prone to conflicts between religions. The objectives are: first, to find out how the implementation of the strategies of religious leaders to maintain harmony between religions. Second, to find out what are the challenges and obstacles for the role of religious leaders and the government itself. Plurality in this study can be seen by the existence of several places of worship, the existence of several cultures and languages. With plurality, it is necessary to have a strategy of religious leaders to always do to give understanding to the community to avoid conflicts related to sara '. Related to the plurality aspect, the strategy adopted by religious leaders in avoiding conflict is by assimulating activities and tolerance of muamalah worship. The nature of the family and social values ​​that have been well established are the existence of equality and mutual need in terms of work. Strategies of Religious Leaders in overcoming conflicts in plural societies certainly have challenges due to disagreements and interests that hamper the role of religious leaders to provide understanding to the community. The challenges experienced are of course the solutions offered, namely the approach to overcoming all of them, namely with persuasive approach, this approach aims to establish a good emotional relationship between characters and the community, so that what is conveyed can be implemented into social life.